School–industry collaboration in vocational education: Partnership management at SMKN Windusari - Hidayah Uswatun Kasanah; Maya Novita Sari; Tarso Tarso; Edi Purwanto (Curricula: Journal of Curriculum Development, 2025)
The partnership between vocational high schools (SMK) and the business and industrial sectors (DUDI) serves as a key strategy in strengthening vocational education to ensure its relevance to labor market demands. This study aims to provide an in-depth description of the partnership management between SMKN Windusari, Magelang Regency, and DUDI, viewed from the aspects of planning, organizing, implementation, and evaluation. A descriptive qualitative approach was used, with data collected through in-depth interviews, observations, and document analysis. The findings indicate that planning was carried out systematically by integrating the partnership programs into official documents such as the School Work Plan (RKS) and the Medium-Term Work Plan (RKJM). Organizing was implemented through the formation of functional teams with clear structures and roles. Implementation involved the utilization of human resources, funding, and school facilities, supported by industry partners. Evaluation was conducted periodically through discussions, activity reports, and review of Memorandums of Understanding (MoU). Main obstacles included limited partners, differing orientations, and technical constraints, which were addressed through adaptive strategies such as network expansion and schedule adjustments. The study recommends enhancing data-based evaluation and strengthening human resource capacity to ensure the sustainability and effectiveness of vocational school–industry partnerships.   Abstrak Kemitraan antara SMK dan Dunia Usaha serta Dunia Industri (DUDI) sebagai strategi penting dalam penguatan pendidikan vokasi yang relevan dengan kebutuhan pasar kerja. Penelitian ini bertujuan untuk mendeskripsikan secara mendalam manajemen kemitraan antara SMKN Windusari Kabupaten Magelang dengan dunia usaha dan dunia industri (DUDI) ditinjau dari aspek perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. Pendekatan yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa perencanaan dilakukan secara sistematis melalui integrasi program kemitraan dalam dokumen RKS dan RKJM, sedangkan pengorganisasian dilaksanakan melalui pembentukan tim fungsional dengan struktur dan tugas yang jelas. Pelaksanaan melibatkan pemanfaatan sumber daya manusia, dana, dan sarana sekolah, serta dukungan dari mitra industri. Evaluasi dilaksanakan secara berkala melalui diskusi, laporan kegiatan, dan peninjauan MoU. Hambatan utama meliputi keterbatasan mitra, perbedaan orientasi, dan kendala teknis, namun diatasi melalui strategi adaptif seperti perluasan jaringan dan penyesuaian jadwal. Penelitian ini merekomendasikan peningkatan kualitas evaluasi berbasis data serta penguatan kapasitas SDM untuk menjamin keberlanjutan dan efektivitas kemitraan vokasi. Kata Kunci: evaluasi berkelanjutan; kemitraan SMK-DUDI; manajemen pendidikan vokasi